A non-peptide NIR fluorescent probe for detection of chymotrypsin and its imaging application. Issue 18 (5th April 2019) - Mu, Shuai; Xu, Yixuan; Zhang, Yintang; Guo, Xiumei; Li, Jian; Wang, Yali; Liu, Xiaoyan; Zhang, Haixia
Abstract : A novel non-peptide NIR fluorescent probe for the detection of chymotrypsin and its imaging application. Abstract : In this work, a turn-on near-infrared fluorescent probe, hemicyanine derivative (CyB), for the highly selective and sensitive detection of chymotrypsin was developed. The probe is fabricated by incorporating a recognition group of 4-bromobutyryl into the hemicyanine skeleton. Upon the nucleophilic substitution reaction of chymotrypsin and the probe, the probe displayed a remarkable fluorescence enhancement and a visible color change under natural light. This property can be utilized for the detection of chymotrypsin with a detection limit (LOD) of 0.013 U mL −1 . Moreover, the cell and in vivo imaging experiments validated that this probe has the potential ability to detect chymotrypsin in biological systems and can provide a promising application prospect for screening chymotrypsin inhibitors.